L’écriture comme prisme. Contraintes et créations des scribes médiévaux - Alain Boureau (L'Atelier du CRH, 2017)
Daniel Fabre made the notion of « ordinary writing » indispensable. This article considers a species within the genus of ordinary writing, the interstitial writing of medieval scribes. The scribal activity is not a mere matter of reproduction; a scribe moves along the spirals of texts. Let’s take four examples from 13th century Franciscan copyists: in one case, an invention in deciphering illuminated the copied text. Somewhere else, in a very long biblical commentary, a brief passage which appeared detrimental to the scribe’s institution was replaced by an extract from an other commentary. Or the philological concern of an other scribe cleverly fills the gaps that may occur in the model from copyist errors because of some homeoteleuton. At last, in order to preserve some ambivalence, this article presents some wild lapsus calami. Those scribes did not partake of an extra-ordinary creation or speculation. But the fascination for writing could attract them. Taking possession of texts in hand and mind led sometimes to some inventiveness and to passions for words and concepts.